Pengaruh Debt To Equity Ratio, Return On Equity dan Earning Per Share Terhadap Harga Saham Perusahaan Real Estate dan Properti yang Terdaftar di Bursa Efek Indonesia - Romy Lawandi; Carunia Mulya Firdausy (Universitas Tarumanagara, 2020)
This study aims to analyze the influence of Debt to Equity Ratio (DER), Return on Equity (ROE), Earning per Share (EPS) simultaneously and partially to Stock Price of real estate and property company that listed on Indonesian Stock Exchange for period 2015-2018. This research use purposive sampling method and obtained 25 real estate and property company as sample. The analysis method used is multiple linear regression through SPSS 24.00 program. Results of this study shows that simultaneously Debt to Equity Ratio (DER), Return on Equity (ROE), Earning per Share (EPS) have significant influence to stock price. While Partially, only Earning per Share has significant influence to stock price. Meanwhile Debt to Equity Ratio and Return on Equity have not significant influence on stock price of real estate and property company that listed on Indonesian Stock Exchange for period 2015-2018